INVESTIGATION OF THE PROPERTIES OF CONCRETE BASED ON NON-FIRING ALKALINE BINDERS (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article deals with the use of film-forming materials for the care of freshly laid concrete based on non-firing alkaline binders, the results of studies to determine the strength, frost resistance and plastic shrinkage of concrete are presented.